Injection of nitrogen-15 into trees to study nitrogen cycling in soil - Pregitzer, Kurt S., author; Paul, Eldor A., author; Horwath, William R., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 1992)
Most 15N dilution techniques disturb either the soil or N-pool size. The objective of this study was to develop a method of labeling the roots of Populus trees with 15N without physically disturbing the soil. Such a method would enable the direct measurement of the flux of 15N from dead roots into the soil organic matter. Leaf and root biomass were labeled by injection of 15N directly into the vessel elements of hybrid Populus trees during their second growing season. The 15N was uniformly distributed throughout the canopy and root system. The rate and amount of 15N turnover from plant tissue can be determined by pool transfer or through differences in plant 15N concentrations. The 15N was detected in the dead-root pool 8 wk after injection, indicating root turnover. Results demonstrate the ability to measure the contribution of fine-root litter to N-cycling processes without disturbing the soil environment.
Keywords: plant residue; N transformation; N processes; 15N; fertilizer